The Articulation of Native Rights in Canadian Law - Jackson, Michael (Allard Research Commons, 1984)
In this article the author reviews the work of a major commission of inquiry established by the Federal Government of Canada in 1974 to consider the environmental, social and economic impact of the then proposed Mackenzie Valley natural gas pipeline on the land and people in the Yukon and the Northwest Territories - Canada's northland. This commission of inquiry, which is commonly referred to as the Mackenzie Valley Pipeline Inquiry, was presided over by Mr. Justice Thomas Berger, a judge of the Supreme Court of British Columbia. One of the principal issues which quickly emerged in the work of the Inquiry was that of the legal and political rights of the aboriginal peoples of the North. One of the most significant contributions of the Inquiry was the establishment of new procedures which permitted a clear and comprehensive articulation by the aboriginal peoples of how they understood their rights. These procedures were not developed on an a priori basis but were derived from the volksgeist and law ways of the aboriginal people. These procedures in turn resulted in the substance of aboriginal rights or, as they are generally termed, "native rights", being given a radical content; radical in the sense that the rights as articulated by native peoples, while much broader than those which have been recognized by Canadian courts, reflected the original principles which had governed the relationships between aboriginal peoples and the European colonialists who came amongst them some 400 years ago. An analysis of the Mackenzie Valley Pipeline Inquiry in the context of the articulation of native rights provides, therefore, an opportunity not only to assess within the sociology of law the important role of commissions of inquiry in developing new procedural forums but also to better understand the close relationship between procedural and substantive rights as revealed in the historical evolution of native rights in Canada.